Feminist stylistics - Mills, Sara 1954- (Interface (London, England), 1995)
Uses language study and linguistic theory to set the rationale for feminist text analysis. The book examines sexism, political correctness, reader positioning, narrative, agency, discourse, character and role analysis. It examines literary texts alongside newspapers, pop songs and advertisements.